Revolution, Evolution and Endurance in Anglophone Literature and Culture - Martynuska, Malgorzata,Rokosz-Piejko, Elzbieta (Peter Lang GmbH, 2016)
The essays collected in this book examine different aspects of change in literature and culture of the Anglophone world. The contributors analyse literary theory as well as individual literary works ranging from John Dryden’s poetry, through the 18th-century English novel, to the 20th-century drama and prose. The contributions also focus on visual arts and film, the socio-political context, and concern various aspects of British and American history, culture and economy.
10.3726/978-3-653-06992-1
Keywords: Aufsatzsammlung; Englisch; Geschichte; Literatur; Revolution; Politik; Kognitive Poetik